TP1-3 Final phase of recruitment and statistics analysis plan for Dex-CSDH trial. Issue 3 (14th February 2019) - Edlmann, E; Kolias, A; Thelin, E; Gatt, D; Al-Tamimi, Y; Owusu-Agyemang, K; Suttner, N; Holton, P; Bulters, D; Allison, A; Bond, S; Tarantino, S; et al.
Abstract : Objectives: Review recruitment progression and statistical analysis plan for Dex-CSDH trial. Design: A UK multi-centre, randomised, double-blind, placebo-controlled trial of dexamethasone versus placebo for CSDH. Subjects: Symptomatic, adult CSDH patients admitted to a participating neurosurgical unit. Methods: Trial participants receive a 2 week course of dexamethasone in addition to standard care, including surgery. The primary outcome measure is the modified Rankin Scale (mRS) at 6 months. An mRS of 0–3 requires the patient to be independently mobile and we have considered this a favourable outcome, with scores 4–6 (non-mobile) as unfavourable. The primary analysis will be performed on an intention-to-treat basis, estimating the absolute difference between the two treatment arms in the proportions achieving a favourable outcome. Secondary analysis will be done with an ordinal analysis of mRS scores and proportional odds logistic regression of the original mRS score adjusting for baseline covariates (age, GCS). Results: 629/750 patients (84%) have been recruited to the Dex-CSDH trial which is on-going as of 20-06-2018. Recruitment progress and follow-up at time of presentation will be reviewed alongside full statistical analysis plan. Conclusions: The Dex-CSDH trial is drawing close to target following excellent recruitment across 22 UK centres. Transparent communication of the statistical analysis plan is essential prior to unblinding of the data. Up-to-date recruitment and primary endpoint completion rates will also be reviewed.